Training course «Higher school psychology and pedagogics» for post-graduate students of Peoples` friendship university of Russia - A V Gagarin (Peoples' Friendship University of Russia (RUDN University), 2009)
In article the concept of an original training course «Higher school psychology and pedagogics», addressed to post-graduate students of various specialities is stated.